Kualitas Laporan Keuangan BUMDES dan Faktor yang mempengaruhinya - Ratmasari, Dwidela Infantriani; Yuliani, Nur Laila; Purwantini, Anissa Hakim (Borobudur Accounting Review, 2021)
The existence of BUMDes can help the government in managing creative and innovative village potential, so that it can open up new jobs and absorb the workforce in rural areas. BUMDes as a village financial institution that meets the needs of micro-scale businesses are required to make financial reports of all business units in a transparent and accountable manner every month. BUMDes are also required to provide reports on the development of their business to the village community at least twice a year through village meetings. This study aims to examine the factors that influence the quality of financial reports. The purpose of this study was to examine the effect of the level of education, work experience, training, use of information technology, and internal control on the quality of financial reports at BUMDes in Magelang Regency. The data used in this study uses primary data obtained by distributing questionnaires. The population in this study were BUMDes in Magelang Regency. The sample selection technique used was purposive sampling and obtained 159 samples of BUMDes in the Magelang Regency area. The data analysis method in this research is Confirmatory Factor Analysis. Hypothesis testing in this study uses multiple linear regression analysis. The results showed that the level of education and use of information technology had no effect on the quality of financial reports. While work experience, training, and internal control have a positive effect on the quality of financial reporter).